2011
DOI: 10.1017/s0007114510004277
|View full text |Cite
|
Sign up to set email alerts
|

The effects of laminarin derived fromLaminaria digitataon measurements of gut health: selected bacterial populations, intestinal fermentation, mucin gene expression and cytokine gene expression in the pig

Abstract: The aim of the present study was to establish the optimum inclusion level of laminarin derived from Laminaria digitata on selected microbial populations, intestinal fermentation, cytokine and mucin gene expression in the porcine ileum and colon. A total of twentyone pigs (mean body weight 17·9 kg) were randomly assigned to one of three dietary treatments: T1 -basal (control) diet, T2 and T3 -basal diets supplemented with laminarin included at 300 and 600 parts per million (ppm), respectively. Selected intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 47 publications
7
66
0
Order By: Relevance
“…In this scenario, we suggest that LAM may be tested in the treatment against this infection, once it interacts directly with Dectin-1, is inert, is efficient as we show here and, among the β-1,3-glucans, the compound obtained from Laminaria digitata has high solubility in water and presents low polydispersity, characteristics that makes this compound desirable to the pharmaceutical industry (60, 61). …”
Section: Discussionmentioning
confidence: 77%
“…In this scenario, we suggest that LAM may be tested in the treatment against this infection, once it interacts directly with Dectin-1, is inert, is efficient as we show here and, among the β-1,3-glucans, the compound obtained from Laminaria digitata has high solubility in water and presents low polydispersity, characteristics that makes this compound desirable to the pharmaceutical industry (60, 61). …”
Section: Discussionmentioning
confidence: 77%
“…However, LPS challenge failed to enhance TNF-a mRNA expression in unchallenged ileum tissue. Smith et al (2011) similarly observed no increase in TNF-a mRNA expression in LPS challenged ileum tissue. Fiu'thermore, Li et al (2005) reported an enhanced TNF-a production by peripheral blood lymphocytes stimulated with LPS in vitro.…”
Section: Discussionmentioning
confidence: 86%
“…In pigs, preterm conditions have been shown to impair MUC2 synthesis, predisposing young piglets to develop necrotizing enterocolitis [50]. Colonic mucin gene expression was influenced by the inclusion of laminarin in the diet [51] while there was no effect of low digestible dietary protein and fermentable carbohydrates [52]. MUC13 belongs to the most abundant MUC genes in the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%